Disseminate and Recurrent Infundibulofolliculitis in Childhood: A Rarely Reported Entity. Issue 1 (January 2015) - Kline, Amy; Relic, John
Abstract Disseminate and recurrent infundibulofolliculitis (DRIF) is a term used to describe a micropapular skin disorder, most commonly occurring in young men with Fitzpatrick skin type V and VI. We present the case of two young Sudanese brothers with a clinical and histologic picture typical of this condition, which has been infrequently reported in children and has not previously been reported in related individuals. The etiology remains uncertain and there is no clear consensus on treatment.